2018
DOI: 10.48550/arxiv.1811.06283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irregular model sets and tame dynamics

Abstract: We study the dynamical properties of irregular model sets and show that the translation action on their hull always admits an infinite independence set. The dynamics can therefore not be tame and the topological sequence entropy is strictly positive. Extending the proof to a more general setting, we further obtain that tame implies regular for almost automorphic group actions on compact spaces.In the converse direction, we show that even in the restrictive case of Euclidean cut and project schemes irregular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Since π ′ is N to one, we conclude that the number of the ergodic measures of X ′ is bounded by N(k − 1) N , and so does X , ending the proof. We mention that to obtain Proposition 3.7 we need to use some result (Proposition 3.2) which is a generalization of the previous one obtained by Fuhrmann, Glasner, Jäger and Oertel [11].…”
Section: A General Criteriamentioning
confidence: 97%
See 3 more Smart Citations
“…Since π ′ is N to one, we conclude that the number of the ergodic measures of X ′ is bounded by N(k − 1) N , and so does X , ending the proof. We mention that to obtain Proposition 3.7 we need to use some result (Proposition 3.2) which is a generalization of the previous one obtained by Fuhrmann, Glasner, Jäger and Oertel [11].…”
Section: A General Criteriamentioning
confidence: 97%
“…Recently, a striking result proved by Fuhrmann, Glasner, Jäger and Oertel solved a long open question, i.e. the authors showed that a minimal tame system is regular [11].…”
Section: The Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In [BLR07, Theorem 1] it is shown that for FLC Delone sets ω in R d the patch counting entropy E pc (ω) equals the topological entropy E(π ω ) of this associated dynamical system. This observation is used for example in [PFS14,FGJO18] in order to define the entropy of FLC Delone sets. In [BLR07] the equivalence of these approaches is used to show that FLC Delone sets with "pure point dynamical spectrum" have 0 patch counting entropy.…”
Section: Introductionmentioning
confidence: 99%